2009
DOI: 10.1016/j.juro.2008.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy for Pathological T3N0M0 Prostate Cancer Significantly Reduces Risk of Metastases and Improves Survival: Long-Term Followup of a Randomized Clinical Trial

Abstract: Purpose Extraprostatic disease will be manifest in one third of men after radical prostatectomy. We present long-term followup of a randomized clinical trial of radiotherapy to reduce risk of subsequent metastatic disease and death. Materials and Methods 431 men with pT3N0M0 prostate cancer were randomized to 60–64 Gy adjuvant radiotherapy or observation. The primary study endpoint was metastasis-free survival. Results Of 425 eligible men, 211 were randomized to observation and 214 to adjuvant radiation. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
762
4
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,137 publications
(818 citation statements)
references
References 19 publications
13
762
4
28
Order By: Relevance
“…Thus, our findings, in particular, regarding the non-significant association of adjuvant RT with disease progression and mortality must be interpreted in light of this study design, particularly as prospective randomized trials have demonstrated a benefit to adjuvant RT on reducing the risk of BCR 4,5,36 and, in one series, mortality. 37 Indeed, we did find here that adjuvant RT was associated with a significant decrease in the risk of the outcome measure receipt of salvage therapy or progression. These data likely reflect the previouslydocumented protective effect of adjuvant RT on BCR, 4,5,36 an outcome measure which has been linked to utilization of secondary cancer treatments.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, our findings, in particular, regarding the non-significant association of adjuvant RT with disease progression and mortality must be interpreted in light of this study design, particularly as prospective randomized trials have demonstrated a benefit to adjuvant RT on reducing the risk of BCR 4,5,36 and, in one series, mortality. 37 Indeed, we did find here that adjuvant RT was associated with a significant decrease in the risk of the outcome measure receipt of salvage therapy or progression. These data likely reflect the previouslydocumented protective effect of adjuvant RT on BCR, 4,5,36 an outcome measure which has been linked to utilization of secondary cancer treatments.…”
Section: Discussionmentioning
confidence: 54%
“…PSA kinetics can help identify these patients [22] but often involve multiple PSA measurements that can result in a delay of secondary therapy. Risk assessment tools that can accurately predict cancer recurrence and progression would allow a more timely institution of additional treatments that might be beneficial for selected patients [23][24][25]. Among the 109 published prediction tools [3], only 8 take advantage of pathologic information gained from RP, and very few of these tools have been validated.…”
Section: Discussionmentioning
confidence: 99%
“…At 10 years, it offers more survival benefit than SPCG4 documented for radical prostatectomy over watchful waiting (8% vs. 5%). 2,13 We have a tremendous opportunity to make a meaningful difference in the lives of our patients and the healthcare system -we just need to listen to the evidence and act accordingly.…”
Section: Andrew Loblaw MD Frcpcmentioning
confidence: 99%
“…There are three RCTs showing improvements in local and biochemical control; 1-3 the study with the longest follow-up (SWOG 8794) also demonstrates improvements in distant metastatic disease-free survival and overall survival. 2 Cancer Care Ontario (CCO) published a systematic review of the literature and clinical practice guideline on the topic showing that all subgroups benefitted in biochemical control and overall survival from ART (and those with seminal vesicle involvement seemed to benefit more not less). 4 It is very interesting to see how this evidence is applied in the pragmatic setting.…”
mentioning
confidence: 99%